RANCANGAN PROFIL LULUSAN MASA DEPAN BAGI PENDIDIDIKAN TINGGI AGROINDUSTRI - Anas Bunyamin; Dwi Purnomo; Wahyu Gunawan; Ida Widianingsih; Wanodyo Sulistyani; Ryan Hara Permana (Department of Agroindustrial Technology, Bogor Agricultural University, 2021)
The profiles of higher education graduates are generally attached to the name of professions as a description of the competencies that are expected to be achieved after carrying out the study process at higher education. In the digital era where disruption has hit various fields, various types of new professions have also evolved accordingly and had different types and characters from previous decades. However, the graduate profile stated in the curriculum documents has not followed the current professions’ development. With the evolution of the economic era since the 1960s to the 2000s, from the agricultural, industrial, creative, to collaborative economies, creates a need to establish a graduate profile that is in line with future needs. It is impossible for higher education actors to offer back outdated graduate profiles that are not relevant to the times in the future. In this research, various changes in the world were analyzed and the competences and roles of new graduates were laid out. This profile was aimed to prepare graduates to implement their knowledge when entering the new era that needs different characteristics of graduates compared with the previous era. The research approach wastransformative research involving various experts in a participatory manner to define the character of the profession and what roles are needed in the future. The research was conducted in the Faculty of Agricultural Industry Technology, Padjadjaran University and several faculties which emphasized the implementation of the Outcome Based Curriculum. This research produces 6 types of future role characters that can be used as a reference for future roles of Agro-industrial Higher Education graduates.Keywords: disruptions, generation’s characteristics, agroindustrial courses, graduate’s profiles.